The last orphan [compact disc, unabridged] - Hurwitz, Gregg (Hurwitz, Gregg. Orphan X novel., 2023)
As a child, Evan Smoak was plucked out of a group home, raised, and trained as an off-the-books assassin for the government as part of the Orphan program. When he broke with the program and went deep underground, he left with a lot of secrets in his head that the government would do anything to make sure never got out. When he remade himself as The Nowhere Man, dedicated to helping the most desperate in their times of trouble, Evan found himself slowly back on the government's radar. Having eliminated most of the Orphans in the program, the government will stop at nothing to eliminate the threat they see in Evan. But Orphan X has always been several steps ahead of his pursuers. Until he makes one little mistake ...